Effect of endurance training on plasma levels of AGRP and HOMA-IR in diabetic rats - Javad Mehrabani; Maryam Sedighianrad; Nasrin Ramezani; Hadi Nobari; Reza Bagheri (Turkish Journal of Kinesiology, 2017)
The hypothalamus is a strong central controller of appetite that secretes different neuropeptides including AGRP. Plasma levels of AGRP are effective in controlling obesity and hunger. Therefore, the current study was performed with the aim of investigating the effect of endurance training on plasma levels of AGRP and HOMA-IR in diabetic rats. The Current study was experimental by posttest and control group. Eighteen male Wistar rats (200-220 grams with 8-10 weeks) were randomly divided into the control group and diabetic training. Eight weeks endurance training program included in the group of animal diabetic training for 5 days per week (15-40) minutes at 50 to 65 percent of vo2max. To determine the serum concentrations of AGRP was used by ELISA. A comparison of two groups showed significantly increased plasma concentrations of AGRP (p=0.006) and insulin resistance index, decreased significantly (p=0.002) compared to the control group after eight weeks, endurance training. According to the results, increased plasma concentrations of AGRP can be attributed to the negative balance caused by training. This agent destroys the body's energy balance and hypothalamus for balancing increases the secretion of AGRP. This neuropeptide is likely will cause higher fat metabolism.